New Weird Fiction and the Anthropocene - Dang, Trang. author. (orcid)0000-0001-8815-8619 Link aut Link
X, 169 p.
Keywords: This book explores the development of ecological awareness in Jeff VanderMeer's New Weird novels, focusing specifically on the Southern Reach (2014-2024) and Borne (2017-2019) series. Examining the New Weird genre as an understudied part of climate fiction, the chapters investigate how these texts' language, content, and form develop unique and fascinating ways in which one can think and live more ecologically. As the first book-length study on VanderMeer's work to contextualize his novels through object-oriented ontology (OOO), an emerging branch of speculative philosophy that investigates how things exist, this work enables a uniquely experimental reading of VanderMeer: one that accentuates how his work unsettles what is perceived as normal and exposes the bounds of human reasoning, as well as how we understand ourselves and our relationships with nonhumans. Dang also engages with interdisciplinarity, situating VanderMeer's work within cultural discourse around the Anthropocene, environmental anthropology, prehistoric archeology, evolutionary biology, and Indigenous studies. Trang Dang is Workforce Skills and Inclusion Executive at the Chartered Institution of Wastes Management, UK. She received her PhD in Arts and Humanities from Nottingham Trent University, UK.